Traditional Medicinal Plants and Healing Incantations of The Tidung Tribe, North Kalimantan - Muhammad Arbain; Gusniati Yeisi; Moh. Wahyu Agang; Zulhafandi Zulhafandi (Department of Anthropology, 2026)
This study aims to explore traditional medicine and healing incantations of the Tidung tribe in North Kalimantan. Key informants were selected through purposive sampling among practitioners of traditional medicine among the Tidung tribe. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The data were analyzed descriptively through data reduction, data display, verification, and triangulation. The results showed that medicinal plants accompanied by incantations (mantras) such as kalancoe pinnata (kekapal) are effective in treating toothache and fever, cat’s whiskers (sumit usi) is effective in treating back pain, betel leaf (buyu) is effective in stopping bleeding (nosebleeds), red onion (bawang lia) is effective in treating colds, and nipa palm (perumpung) is effective in treating broken bones These findings show that the traditional medicine system of the Tidung tribe in North Kalimantan, which uses incantations or prayers in the local language, Malay, and Arabic, ending with prayers for healing to God and salawat to the Prophet, still exists amid the rapid development of modern medicine. However, there needs to be strategic inheritance to the younger generation that is more dialogical and inclusive, so that traditional medicine does not appear exclusive.